2016
DOI: 10.1187/cbe.15-07-0144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Dissection Video Clip on Anxiety, Affect, and Self-Efficacy in Educational Dissection: A Treatment Study

Abstract: A predissection video to instruct students about fish dissection was used in a treatment-control study. The dissection film group scored higher in positive affect, negative affect, anxiety, and self-efficacy after the dissection. The dissection film has clear benefits—increasing positive affect and self-efficacy—that come at the cost of higher negative affect and state anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
2
15
0
4
Order By: Relevance
“…The students demonstrated significant gains in self-assessed confidence across all six categories (ES > 1.0 for all; table 6). These changes suggest that CREATE courses promote self-efficacy with respect to science process skills, an area of increasing focus in STEM (Trujillo and Tanner 2014, Connell et al 2016, Kenyon et al 2016, Randler et al 2016). As was described by Bandura (1977), self-efficacy reflects an internal measure of a student's confidence in the ability to complete or perform a goal-directed task within a particular domain.…”
Section: Statistical Analysis Of Student Datamentioning
confidence: 99%
“…The students demonstrated significant gains in self-assessed confidence across all six categories (ES > 1.0 for all; table 6). These changes suggest that CREATE courses promote self-efficacy with respect to science process skills, an area of increasing focus in STEM (Trujillo and Tanner 2014, Connell et al 2016, Kenyon et al 2016, Randler et al 2016). As was described by Bandura (1977), self-efficacy reflects an internal measure of a student's confidence in the ability to complete or perform a goal-directed task within a particular domain.…”
Section: Statistical Analysis Of Student Datamentioning
confidence: 99%
“…Randler et al . ( 20 ) conducted an experimental study on the effect of video demonstration on perceived student anxiety and performance. The authors found watching video demonstrations before the actual dissection reduced student anxiety and improved self-efficacy compared with the group of students who did not watch the dissection video demonstration.…”
Section: Recommendationsmentioning
confidence: 99%
“…El papel clave que juega la innovación educativa en el desarrollo y mejora de los procesos de enseñanza-aprendizaje, el comportamiento innovador de los individuos, organizaciones y economías, sin embargo, poco se ha explorado en la literatura educativa (Maritz et ál., 2014;Richmond y Tatto, 2016) sobre las características y tipología de las innovaciones educativas producidas en los diferentes contextos sociales, así como el alcance e impacto que dichas innovaciones tienen para los agentes del proceso educativo. En el mismo sentido, Ramírez (2012) subraya la importancia que tienen las estrategias de enseñanza-aprendizaje, consideradas como los planteamientos conjuntos de las directrices que determinan actuaciones concretas en cada una de las fases del proceso educativo. Estas estrategias pueden ir desde un gran marco general, como las planteadas en las políticas educativas (que, a su vez, depende de la política general del país donde se encuadran) y conducen al establecimiento detallado de una planificación educativa, hasta las estrategias micro que sigue un docente o una docente en su ambiente de aprendizaje.…”
Section: Introductionunclassified
“…Uso de las tecnologías innovadoras. Esta línea se interesa por documentar el impacto de las tecnologías innovadoras en el aprendizaje de los estudiantes Randler, Demirhan, Wüst-Ackermann, y Desch, 2016), estas tecnologías aparecen como un componente mediador importante del proceso innovador, y si bien su incorporación en las organizaciones educativas es incipiente requiere de estrategias pedagógicas planificadas para la consecución de cambios en el proceso educativo, ya que por sí solas no encaminan hacia el progreso y la innovación; es necesario que existan estrategias políticas y organizacionales .…”
unclassified